Advancements in all-solid-state hybrid solar cells based on organometal halide perovskites. Issue 4 (22nd July 2015) - Shi, Shaowei; Li, Yongfang; Li, Xiaoyu; Wang, Haiqiao
<x xml:space="preserve">Abstract</x> Over the past several years, organic–inorganic hybrid perovskites have gained considerable research attention due to their direct band gap, large absorption coefficient, ambipolar diffusion and long carrier diffusion length, and have revolutionized the prospects of emerging photovoltaic technologies, with the highest power conversion efficiency of over 19% achieved under laboratory conditions.